Late-onset of eruptive syringomas: a diagnostic challenge - Resende, C (2015)
Syringoma is a benign, adnexal tumor of the eccrine sweat gland ducts. Eruptive syringomas are a rare variant, occurring before or during puberty in most cases. A 57-year-old man was observed in our department, with a 10-year history of multiple brownish papules (1-4mm in diameter), localized on the neck, shoulders, trunk and axillae. The clinical diagnosis was cutaneous mastocytosis. Histopathological examination from a papule in the trunk was compatible with the diagnosis of syringoma. The patient was treated with isotretinoin, without any improvement. The clinical diagnosis of eruptive syringoma is difficult and histological examination is crucial for its diagnosis. Long-term morbidity is not associated with syringomas; they are treated for cosmetic reasons with unsatisfactory results.